Original paperEmotional intelligence as an indicator of satisfaction with life of patients with psoriasis - Basińska, Małgorzata A.; Drozdowska, Marta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : Research reports confirm the existence of a relation between emotional intelligence and various aspects of human functioning. It protects psychical and physical health of an individual, helps to adapt to new conditions and, consequently, contributes to the increase in life quality expressed in satisfaction with life. Psoriasis, a chronic skin disease, may negatively influence the psychical state of a patient and his or her social functioning, which leads to the decrease in satisfaction with life. Aim: This research aimed at determining the relation between emotional intelligence and satisfaction with life in a group of patients with psoriasis. Material and methods : The research group consisted of 81 people with psoriasis (40 men and 41 women) with the average age of 41.22 (SD = 14.18). The research tools used included the Emotional Intelligence Questionnaire INTE, Satisfaction With Life Scale (SWLS), personal questionnaire and PASI scale. Results : There is a positive correlation between emotional intelligence and satisfaction with life in the group of patients with psoriasis. Especially factor I – using emotions in thinking and operating – positively correlates with satisfaction with life. Conclusions : Emotional intelligence together with the percentage of body area taken by pathological changes are the indicators of satisfaction with life in patients with psoriasis.